(untitled) (Mantichora. Italian Journal of Performance Studies, 2021)
In this essay we consider how the macabre dance, probably born within the Churches as a homiletical illustration, would adopt a choreutic model characteristic of the most common ecclesiastical dances. The conduit was the usual way to conduct the dance around the relics of the saints, as in the case of the Canzon de santa Fe in Concas as early as the 11th century, which would have given rise to an architectural space such as the ambulatory or processional corridor that surrounded the statue or the remains of the venerated saint. A dance in a row that characterizes the first iconographic examples of the macabre dance, where the dead follow one another in a hierarchically organized chain and alternating with their living correspondent. A chain that could be closed in a circle, like the famous carols, which sometimes appear in the iconography surrounding the sarcophagus of a dead man. A line that is enclosed in a circle and reopens to continue an itinerary that could go beyond the limits of the temple and spread through the streets and squares of the town. A dance that became traditional and which is already documented in the fifteenth century, the contrapàs, would respond to this model, and so it has been preserved until today in the Catalan territory. The contrapàs, a solemn and archaic dance performed in the eighteenth century and which was interpreted with the song of the story of the Passion, forms a row of dancers who evolve in the square and which occasionally transforms into a circle, whose ending must allow in the same point where they started. Due to its shape and its evolutions, the contrapàs seems to us the latest echo of the choreutic model of the late medieval macabre dances.